Driving Employees ‘Engagement and Well-Being in the "New Normal“ Times - Tatjana JOVANOVIC; Marija LUGONJIC (Communications of International Proceedings, 2021)
Aside from the fourth industrial revolution and many disruptive changes, the global COVID-19 pandemic has brought additional challenges. It has severely affected workplaces and employees physically through social distancing, but also mentally. The uncertainties of the pandemic, with a threat to physical health combined with unexpected and sudden changes in personal and professional lives, have led many people in the workforce to experience various negative emotions, affecting their motivation level and engagement. An adequate response to the challenges above should facilitate the company’s transition from a “new normal” to a “new future”. HR department should have the key role in this facilitation when an organization faces serious challenges with a potential threat to its business, yet it is not uncommon for HR to be seen as a “luxury” and thus to be the first to be hit with the budget “cuts”. This paper aims to present a framework for implementing the company’s measures to support employees in this “new normal”, by creating a positive impact on their well-being, engagement and thus company performance. The backbone of the article is a case study that places special emphasis on actions in the field of human resources (HR), as well as on the impact they can have on employees, their engagement and consequently, on the entire organization, including its business. The presented illustrative case study with findings can help organizations to adopt novel ways to support their employees in adapting, building resilience and staying committed towards their work in “new normal” times.
Keywords: employees’ engagement; well -being; HR; “new normal “; new”future”